Oxygen-nitrogen co-doped hollow carbon nanoparticles, preparation method thereof, and application thereof in electrosynthesis of hydrogen peroxide
By using the PECVD method to prepare oxygen and nitrogen co-doped hollow carbon nanoparticles in electrocatalytic synthesis of hydrogen peroxide, the problems of insufficient catalyst performance and complex preparation methods in the prior art are solved, and electrocatalytic performance with high selectivity, activity and stability are achieved.
Patent Information
- Application Number
- CN202411603601.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-12
AI Technical Summary
In the existing electrocatalytic synthesis of hydrogen peroxide technology, the development of high-performance oxygen reduction catalysts is difficult to meet the requirements of high selectivity and long life at high current density, and the commonly used doping methods are complex, time-consuming and unfavorable for environmental protection and industrial production.
Plasma enhanced chemical vapor deposition (PECVD) method is used to deposit in an oxygen-containing atmosphere and a nitrogen atmosphere separately to prepare oxygen-nitrogen co-doped hollow carbon nanoparticles. By adjusting the proportion and geometric configuration of doped oxygen and nitrogen, the electrocatalytic performance of carbon materials is optimized.
The selectivity and electrocatalytic activity of hydrogen peroxide are significantly improved (half-wave potential is reduced by about 100mV), and the stability is maintained at high current density. The preparation method is simple, efficient, and environmentally friendly, suitable for industrial production.
Smart Images

Figure CN119118110B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to oxygen-nitrogen co-doped hollow carbon nanoparticles, a preparation method thereof, and application thereof in electrosynthesis of hydrogen peroxide. Background Art
[0002] Hydrogen peroxide is one of the 100 most important chemicals in the world and is widely used in various fields such as chemical synthesis, water treatment, bleaching and disinfection. In terms of its synthesis method, the energy-saving and environmentally friendly electrocatalytic two-electron oxygen reduction synthesis of hydrogen peroxide technology is considered to be an effective way to replace the traditional high-energy consumption and high-pollution anthraquinone process. In order to meet the economic feasibility of industrial production, the electrosynthesis of hydrogen peroxide process needs to be carried out at a high current density (>100mA / cm 2 ) while maintaining high hydrogen peroxide selectivity and long life. Therefore, one of the core issues of electrosynthetic hydrogen peroxide technology is the development of high-performance oxygen reduction catalysts, which fundamentally determines the energy efficiency and economy of the entire electrolysis process.
[0003] A large number of studies have shown that cheap carbon materials are a feasible catalyst for oxygen reduction to hydrogen peroxide with good catalytic performance. Increasing the specific surface area of the catalyst, that is, increasing the number of exposed active sites, is the simplest and most efficient solution to enhance electrocatalytic activity. For example, Chinese patent CN117431559A "A highly selective H2O2 electrosynthesis carbon-based catalyst and its preparation method and application" selects mesoporous carbon with a high specific surface area as the raw material for catalytic modification. In order to further enhance the intrinsic electrocatalytic activity, a commonly used feasible method is to introduce non-metallic heteroatoms such as oxygen, nitrogen and boron on the carbon surface to adjust the electronic structure of adjacent carbon atoms, optimize the adsorption energy of key oxygen species (*OOH) intermediates in the oxygen reduction reaction, and enhance the catalytic activity and selectivity of carbon materials (Nano-Micro Letters. 2023, 15,122). For example, Chinese patent CN 115852424A discloses "the application of an oxygen-doped carbon material in the electrocatalytic synthesis of hydrogen peroxide", and Chinese patent CN117144395A3 discloses "a preparation method and application of a boron / nitrogen co-doped carbon catalyst for the electrocatalytic synthesis of hydrogen peroxide". The above-mentioned carbon materials have significantly improved the performance of electrosynthesizing hydrogen peroxide after doping modification. However, the doping method used is complicated and time-consuming (about 15h), and it also requires the use of high temperature (400-900℃) high pressure environment and highly corrosive acid reagents, which is not conducive to environmental protection and the promotion of industrial production. To solve the above problems, Chinese patent CN117926285A discloses "a plasma oxygen-doped activated carbon catalyst and its preparation method and application". The invention uses high-energy oxygen plasma as a reactant, and prepares a series of oxygen-doped activated carbon catalysts at room temperature by adjusting the reaction time (10-40min) and reaction power (100-300W). Although this method can improve the selectivity of hydrogen peroxide to a certain extent, the improvement on electrocatalytic activity is quite limited. Summary of the invention
[0004] The object of the present invention is to provide an oxygen-nitrogen co-doped hollow carbon nanoparticle and a preparation method thereof and application in the electrosynthesis of hydrogen peroxide. The oxygen-nitrogen co-doped hollow carbon nanoparticle has excellent two-electron oxygen reduction electrocatalytic activity, hydrogen peroxide selectivity and stability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing oxygen-nitrogen co-doped hollow carbon nanoparticles, comprising the following steps:
[0007] Using plasma enhanced chemical vapor deposition method:
[0008] In an oxygen-containing atmosphere, carbon nanoparticles are first deposited, and oxygen-doped hollow carbon nanoparticles are obtained by ablation of oxygen-containing plasma;
[0009] In a nitrogen-containing atmosphere, subjecting the oxygen-doped hollow carbon nanoparticles to a second deposition to obtain oxygen-nitrogen co-doped hollow carbon nanoparticles;
[0010] The surface graphite layer thickness of the oxygen-nitrogen co-doped hollow carbon nanoparticles is 5 to 100 atomic layers, and the cavity width is 5 to 50 nm;
[0011] In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of the doped oxygen atoms is 1-12%, and the molar content of the carbonyl oxygen atoms in the doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 0.5-3%; the XPS binding energy of the carbonyl oxygen is BE=531.0 eV;
[0012] The content x of the carbonyl oxygen atom and the electrocatalytic activity y satisfy the following functional relationship: y=0.058x+0.61, R 2 =0.90; where y is the half-wave potential E 1 / 2 V vs. RHE meter;
[0013] In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped nitrogen atoms is 1-4%, the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounts for 50-80% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 0.5-2:1.
[0014] Preferably, the carbon nanoparticles are conductive carbon black, and the particle size of the conductive carbon black is 10-200 nm.
[0015] Preferably, the oxygen-containing atmosphere includes one or more of oxygen-argon, carbon dioxide-argon, and water vapor-argon.
[0016] Preferably, the volume fraction of argon in the oxygen-containing atmosphere is 50-90%; and the flow rate of the oxygen-containing atmosphere is 20-200 mL / min.
[0017] Preferably, the surface graphite layer thickness of the oxygen-nitrogen co-doped hollow carbon nanoparticles is 5 to 100 atomic layers, and the cavity width is 5 to 50 nm.
[0018] Preferably, the nitrogen-containing atmosphere includes nitrogen or ammonia; the flow rate of the nitrogen-containing atmosphere is 20-200 mL / min.
[0019] Preferably, the conditions of the first deposition and the second deposition independently include: plasma RF power of 100-500 W, vacuum degree of 10-100 Pa, sample tube speed of 50-100 rpm, temperature of 25-500° C., and time of 10-60 min.
[0020] The present invention provides oxygen-nitrogen co-doped hollow carbon nanoparticles prepared by the preparation method described in the above technical solution.
[0021] The present invention provides application of the oxygen-nitrogen co-doped hollow carbon nanoparticles described in the above technical solution in electrosynthesis of hydrogen peroxide.
[0022] The present invention provides a method for preparing oxygen-nitrogen co-doped hollow carbon nanoparticles. The present invention adopts a plasma enhanced chemical vapor deposition (PECVD) method, takes a carbon material as a substrate, firstly bombards the surface of the carbon material with high-energy plasma particles generated by radio frequency excitation in an oxygen-containing atmosphere, forces the carbon-carbon bond in the carbon material to break, and produces a strong ablation effect on the carbon graphite layer, thereby forming a hollow carbon structure with a high specific surface area, which can greatly increase the effective electrocatalytic specific surface area; and a large number of oxygen atoms can be introduced during the ablation of the graphite layer, and its geometric configuration can be adjusted by the type of excited atmosphere and the reaction temperature, thereby obtaining oxygen-doped hollow carbon nanoparticles with excellent electrocatalytic performance; after the oxygen doping reaction is completed, the oxygen-containing atmosphere is switched to a nitrogen-containing atmosphere, and an oxygen-nitrogen co-doped hollow carbon nanoparticle catalyst is prepared, which can be used for electrocatalytic synthesis of hydrogen peroxide. The oxygen-nitrogen co-doped hollow carbon nanoparticles prepared by the present invention not only improve the selectivity of hydrogen peroxide, but also greatly improve the electrocatalytic activity (the half-wave potential is reduced by about 100mV). This is because: first, the prepared carbon nanomaterial has a hollow structure, which greatly increases the active area of the catalyst, which means that the active sites involved in the catalytic reaction are increased and is beneficial to the mass transfer process of the reaction; second, oxygen and nitrogen doping can optimize its intrinsic catalytic performance and accelerate the reaction kinetics.
[0023] The present invention can regulate the morphological characteristics of carbon nanoparticles and introduce the geometric configuration of oxygen and nitrogen atoms on the carbon surface by changing the process parameters (gas source type, temperature and power), thereby greatly improving its electrocatalytic oxygen reduction reaction activity and hydrogen peroxide selectivity, and obtaining high-performance oxygen-nitrogen co-doped hollow carbon nanoparticles.
[0024] The preparation method of the invention is simple, efficient, environmentally friendly and conducive to industrial production.
[0025] The oxygen-nitrogen co-doped hollow carbon nanoparticles prepared by the present invention are subjected to high current density (300 mA / cm 2 ) can operate stably for more than 100 h under low temperature and high pressure, and can maintain a current efficiency of 90~100%. It has excellent two-electron oxygen reduction electrocatalytic activity, hydrogen peroxide selectivity and stability.
[0026] The present invention uses the PECVD method to adjust the proportion of introduced oxygen atoms to further optimize the activity and selectivity of the electrocatalytic oxygen reduction of carbon materials. At the same time, the PECVD method is used to accurately control the geometric configuration of oxygen and nitrogen doping, thereby achieving controllable oxygen and nitrogen doping and optimizing the intrinsic catalytic performance of carbon nanomaterials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The oxygen reduction polarization curves and hydrogen peroxide selectivity curves of different carbon materials are shown;
[0028] Figure 2 TEM images of different carbon materials;
[0029] Figure 3 Double layer capacitance diagrams of different carbon materials;
[0030] Figure 4 O1s fine spectra of different carbon materials;
[0031] Figure 5 is a graph showing the relationship between the carbonyl content and the electrocatalytic activity in the initial carbon material and the oxygen-doped carbon material prepared in Examples 1 to 9;
[0032] Figure 6 N1s fine spectra of different carbon materials;
[0033] Figure 7 O1s and N1s spectra of oxygen-nitrogen co-doped hollow carbon nanoparticles prepared in Example 16;
[0034] Figure 8 The cell pressure and hydrogen peroxide selectivity of the oxygen-nitrogen co-doped hollow carbon nanoparticles prepared in Example 16 vary with time;
[0035] Fig. 9 The figure is a schematic diagram of the preparation process of oxygen-nitrogen co-doped hollow carbon nanoparticles of the present invention. DETAILED DESCRIPTION
[0036] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0037] The present invention provides a method for preparing oxygen-nitrogen co-doped hollow carbon nanoparticles, comprising the following steps:
[0038] Using plasma enhanced chemical vapor deposition method:
[0039] In an oxygen-containing atmosphere, carbon nanoparticles are first deposited, and oxygen-doped hollow carbon nanoparticles are obtained by ablation of oxygen-containing plasma;
[0040] In a nitrogen-containing atmosphere, subjecting the oxygen-doped hollow carbon nanoparticles to a second deposition to obtain oxygen-nitrogen co-doped hollow carbon nanoparticles;
[0041] The surface graphite layer thickness of the oxygen-nitrogen co-doped hollow carbon nanoparticles is 5 to 100 atomic layers, and the cavity width is 5 to 50 nm;
[0042] In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of the doped oxygen atoms is 1-12%, and the molar content of the carbonyl oxygen atoms in the doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 0.5-3%; the XPS binding energy of the carbonyl oxygen is BE=531.0 eV;
[0043] The content x of the carbonyl oxygen atom and the electrocatalytic activity y satisfy the following functional relationship: y=0.058x+0.61, R 2 =0.90; where y is the half-wave potential E 1 / 2 V vs. RHE meter;
[0044] In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped nitrogen atoms is 1-4%, the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounts for 50-80% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 0.5-2:1.
[0045] In the present invention, the carbon nanoparticles are preferably conductive carbon black, and the particle size of the conductive carbon black is preferably 10 to 200 nm. The present invention has no particular limitation on the source of the conductive carbon black, and any commercial conductive carbon black known in the art can be used.
[0046] The present invention has no particular limitation on the amount of the carbon nanoparticles used, which can be adjusted according to actual needs, and a more preferred amount added in a single batch is 1-10 g.
[0047] In the present invention, the oxygen-containing atmosphere preferably includes one or more of oxygen-argon, carbon dioxide-argon, and water vapor-argon. When the oxygen-containing atmosphere is two or more of the above, it is preferably adjusted according to actual needs to ensure its oxygen content.
[0048] In the present invention, the volume fraction of argon in the oxygen-containing atmosphere is preferably 50-90%, more preferably 60-80%; the flow rate of the oxygen-containing atmosphere is preferably 20-200 mL / min, more preferably 100-150 mL / min.
[0049] In the present invention, the conditions of the first deposition preferably include: plasma RF power of 100-500W, vacuum degree of 10-100Pa, sample tube rotation speed of 50-100rpm, temperature of 25-500°C, and time of 10-60min. The plasma RF power is more preferably 100-200W, the vacuum degree is more preferably 40-60Pa, the sample tube rotation speed is more preferably 60-80rpm, the temperature is more preferably 100-300°C, and the time is more preferably 20-40min. The heating rate to the temperature of the first deposition is preferably 10°C / min.
[0050] In the present invention, the surface graphite layer thickness of the oxygen-nitrogen co-doped hollow carbon nanoparticles is 5 to 100 atomic layers, and the cavity width is 5 to 50 nm.
[0051] The present invention uses solid commercial carbon material as a substrate, and utilizes PECVD radio frequency to excite an oxygen-containing atmosphere to generate a super-strong oxidizing oxygen-containing plasma to ablate the graphite layer in the carbon. During the graphite layer ablation process, oxygen atoms are introduced into the graphite layer of the carbon to obtain oxygen-doped hollow carbon nanoparticles with a specific morphology.
[0052] In the present invention, the nitrogen-containing atmosphere preferably includes nitrogen or ammonia; the flow rate of the nitrogen-containing atmosphere is preferably 20 to 200 mL / min, more preferably 50 to 150 mL / min, and further preferably 60 to 120 mL / min.
[0053] In the present invention, the conditions of the second deposition preferably include: plasma RF power of 100-500W, vacuum degree of 10-100Pa, sample tube rotation speed of 50-100rpm, temperature of 25-500°C, and time of 10-60min. The plasma RF power is more preferably 100-200W, the vacuum degree is more preferably 40-60Pa, further preferably 50Pa, the sample tube rotation speed is more preferably 60-80rpm, the temperature is more preferably 100-300°C, and the time is more preferably 20-40min.
[0054] The present invention allows oxygen-doped hollow carbon nanoparticles to react again with nitrogen plasma excited by PECVD through a second deposition, and prepares oxygen-nitrogen co-doped hollow carbon nanoparticles with adjustable ratios of pyridine nitrogen and pyrrole nitrogen by controlling the reaction temperature.
[0055] like Fig. 9 As shown, the present invention preferably places the carbon material in a quartz tube reactor, continuously introduces oxygen-containing gas; turns on the vacuum pump, evacuates to the required vacuum degree; heats the quartz tube to the reaction temperature, turns on the plasma radio frequency power supply; after a specific reaction time, turns off the radio frequency power supply; after naturally cooling to room temperature, turns off the vacuum pump and airflow; and collects the material in the quartz tube. To ensure the uniformity of the carbon material modification, the quartz tube is continuously rotated during the reaction.
[0056] The present invention provides oxygen-nitrogen co-doped hollow carbon nanoparticles prepared by the preparation method described in the above technical solution.
[0057] In the present invention, the molar content of the doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 1-12%, preferably 6-10%, and the molar content of the carbonyl oxygen atoms in the doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 0.5-3%, preferably 2-3%; the XPS binding energy of carbonyl oxygen is BE=531.0 eV;
[0058] In the present invention, the content x of the carbonyl oxygen atom and the electrocatalytic activity y satisfy the following functional relationship: y=0.058x+0.61, R 2 =0.90; where y is the half-wave potential E 1 / 2 V vs. RHE meter.
[0059] In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped nitrogen atoms is 1-4%, preferably 2-3%, the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms is 50-80%, preferably 70-80%, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 0.5-2:1, preferably 1-1.5:1.
[0060] The present invention provides the use of the oxygen-nitrogen co-doped hollow carbon nanoparticles in the above technical solution in the electrosynthesis of hydrogen peroxide. The present invention has no special limitation on the method of the application, and the application can be carried out according to methods well known in the art.
[0061] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0062] Example
[0063] The carbon black powder used in the following examples is conductive carbon black with a particle size of 10 to 200 nm.
[0064] 1. Oxygen-doped carbon materials
[0065] The effects of PECVD process parameters on the configuration of introduced oxygen atoms and catalyst performance were verified by three-factor and three-level orthogonal experiments:
[0066] Factor 1 = atmosphere (O2 / Ar, CO2 / Ar, H2O / Ar);
[0067] Factor 2 = temperature (25°C, 100°C, 300°C);
[0068] Factor 3 = Power (100W, 300W, 500W).
[0069] Table 1 Orthogonal experimental parameters of Examples 1 to 9
[0070]
[0071] Example 1
[0072] 1) Accurately weigh 10 g of carbon black powder (XC-72R, Cabot Corporation), place it in a quartz tube reactor (PECVD equipment model is ZH-1000M), and then keep the quartz tube rotating at a constant speed of 60 rpm;
[0073] 2) Continue to introduce a mixed gas of oxygen / argon (the volume fraction of argon is 50%) with a total gas flow rate of 100 mL / min; turn on the vacuum pump and evacuate to a vacuum degree of 50 Pa;
[0074] 3) Turn on the plasma RF power, react at 100W RF power for 10 minutes, and then turn off the RF power;
[0075] 4) Turn off the vacuum pump and the mixed gas flow control valve, and turn on the argon flushing mode to restore the quartz tube to normal pressure; collect the reaction products to obtain oxygen-doped carbon material.
[0076] Example 2
[0077] The only difference from Example 1 is that: before starting step 3), the quartz tube needs to be heated to 100° C.; and the radio frequency power used in step 3) is 500W.
[0078] Example 3
[0079] The only difference from Example 1 is that: before starting step 3), the quartz tube needs to be heated to 300° C.; the radio frequency power used in step 3) is 300W.
[0080] Example 4
[0081] The only difference from Example 1 is that the mixed gas used in step 2) is carbon dioxide and argon (the volume fraction of argon is 50%); and the radio frequency power used in step 3) is 500W.
[0082] Example 5
[0083] The only differences from Example 1 are that the mixed gas used in step 2) is carbon dioxide and argon (the volume fraction of argon is 50%); before starting step 3), the quartz tube needs to be heated to 100°C; and the RF power used in step 3) is 300W.
[0084] Example 6
[0085] The only difference from Example 1 is that the mixed gas used in step 2) is carbon dioxide and argon (the volume fraction of argon is 50%); before starting step 3), the quartz tube needs to be heated to 300°C; and the RF power used in step 3) is 100W.
[0086] Example 7
[0087] The only difference from Example 1 is that: wet argon gas with a flow rate of 100 mL / min is used (the argon gas flows through the gas washing bottle to carry water vapor, and the volume fraction of argon gas is 50%); the RF power used in step 3) is 300 W.
[0088] Example 8
[0089] The only difference from Example 1 is that wet argon gas with a flow rate of 100 mL / min is used (the argon gas flows through the gas washing bottle to carry water vapor, and the volume fraction of argon gas is 50%); before starting step 3), the quartz tube needs to be heated to 100°C, and the RF power used in step 3) is 100 W.
[0090] Example 9
[0091] The only difference from Example 1 is that wet argon gas with a flow rate of 100 mL / min is used (the argon gas flows through the scrubbing bottle to carry water vapor, and the volume fraction of argon gas is 50%); before starting step 3), the quartz tube needs to be heated to 300°C, and the RF power used in step 3) is 500 W.
[0092] 2. Nitrogen-doped carbon materials
[0093] Using high-energy nitrogen plasma as the nitrogen source, the effects of reaction temperature and RF power on the geometric configuration of introduced nitrogen atoms and catalyst performance were studied:
[0094] Example 10
[0095] 1) Accurately weigh 10 g of carbon black powder (XC-72R, Cabot Corporation) and place it in a quartz tube reactor (PECVD equipment model is ZH-1000M), and then keep the quartz tube rotating at a constant speed of 60 rpm;
[0096] 2) Continue to introduce nitrogen at a flow rate of 100 mL / min; turn on the vacuum pump and evacuate to a vacuum degree of 50 Pa;
[0097] 3) Turn on the plasma RF power, react at 100W RF power for 20 minutes, and then turn off the RF power;
[0098] 4) Turn off the vacuum pump and the mixed gas flow control valve; and turn on the argon flushing mode to restore the quartz tube to normal pressure; collect the reaction products to obtain nitrogen-doped carbon material.
[0099] Embodiment 11
[0100] The only difference from Example 10 is that the radio frequency power used in step 3) is 300W.
[0101] Example 12
[0102] The only difference from Example 10 is that the radio frequency power used in step 3) is 500W.
[0103] Embodiment 13
[0104] The only difference from Example 10 is that before starting step 3), the quartz tube needs to be heated to 100°C, and the radio frequency power used in step 3) is 100W.
[0105] Embodiment 14
[0106] The only difference from Example 10 is that before starting step 3), the quartz tube needs to be heated to 300°C, and the radio frequency power used in step 3) is 100W.
[0107] 3. Oxygen / nitrogen co-doped carbon materials
[0108] Embodiment 15
[0109] 1) Accurately weigh 10 g of carbon black powder (XC-72R, Cabot Corporation) and place it in a quartz tube reactor (PECVD equipment model is ZH-1000M), and then keep the quartz tube rotating at a constant speed of 60 rpm;
[0110] 2) Continue to introduce a mixed gas of carbon dioxide and argon (the volume fraction of argon gas is 50%) at a flow rate of 100 mL / min; then heat the tube furnace to 300°C at a heating rate of 10°C / min; turn on the vacuum pump and evacuate to a vacuum degree of 50 Pa;
[0111] 3) Turn on the plasma RF power supply, react at 100W RF power for 10 minutes, and then turn off the RF power supply and the tube furnace power supply;
[0112] 4) Switch the mixed gas to high-purity nitrogen (purity of 99.99%) with a flow rate of 100 mL / min; after the tube furnace cools to 25°C, turn on the RF power, react at 50 Pa and 100 W RF power for 20 minutes, and then turn off the RF power;
[0113] 5) turning off the vacuum pump and the airflow control valve, and turning on the argon flushing mode to restore the quartz tube to normal pressure, collecting the reaction products, and obtaining oxygen-nitrogen co-doped hollow carbon nanoparticles; wherein the molar content of doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 10.9%, and the molar content of carbonyl oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 2.1%; the molar content of doped nitrogen atoms is 1.8%, the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounts for 68.9% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 0.6:1.
[0114] Example 16
[0115] 1) Accurately weigh 10 g of carbon black (XC-72R, Cabot Corporation) and place it in a quartz tube reactor (PECVD equipment is ZH-1000M model), and then keep the quartz tube rotating at a constant speed of 60 rpm;
[0116] 2) Continue to introduce a mixed gas of carbon dioxide and argon (the volume fraction of argon gas is 50%) at a flow rate of 100 mL / min; then heat the tube furnace to 300°C at a heating rate of 10°C / min; turn on the vacuum pump and evacuate to a vacuum degree of 50 Pa;
[0117] 3) Turn on the plasma RF power, react at 100W RF power for 10 minutes, and then turn off the RF power;
[0118] 4) Switch the mixed gas to high-purity nitrogen (purity of 99.99%) with a flow rate of 100 mL / min, wait for ten minutes (until the carbon dioxide and argon in the quartz tube are completely discharged), turn on the RF power, react for 20 minutes at 50 Pa, 300 ° C, and 100 W RF power, and turn off the RF power;
[0119] 5) After the quartz tube and the radio frequency electrode are naturally cooled to room temperature, the vacuum pump and the airflow control valve are turned off, and the argon flushing mode is turned on to restore the quartz tube to normal pressure; the reaction products are collected to obtain oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped oxygen atoms is 10.1%, and the molar content of carbonyl oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 2.3%; the molar content of doped nitrogen atoms is 2.1%, and the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms is 75.2% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 1.5:1.
[0120] Embodiment 17
[0121] The only difference from Example 16 is that: in step 3), the reaction was carried out at 100 W RF power for 20 minutes. In the prepared oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped oxygen atoms was 11.2%, and the molar content of carbonyl oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles was 2.4%; the molar content of doped nitrogen atoms was 2.3%, and the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounted for 76.7% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen was 1.4:1.
[0122] Embodiment 18
[0123] The only difference from Example 16 is that: in step 3), the reaction was carried out at 100 W RF power for 40 minutes. In the prepared oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of doped oxygen atoms was 11.6%, and the molar content of carbonyl oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles was 2.3%; the molar content of doped nitrogen atoms was 1.9%, and the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounted for 74.9% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen was 1.6:1.
[0124] Catalytic performance test
[0125] The carbon materials prepared in different embodiments were used as catalysts to test their catalytic performance
[0126] 1. Three-electrode rotating ring disk electrode test (RRDE, evaluating intrinsic electrocatalytic performance):
[0127] Polishing and cleaning of glassy carbon electrode: polish and clean the glassy carbon electrode step by step with alumina polishing powder of different particle sizes (1, 0.3, 0.05µm). After each polishing stage, clean the surface of the glassy carbon electrode with a large amount of ultrapure water and ultrasonicate for 30s to remove the residual alumina powder; blow dry with a nitrogen gun and set aside.
[0128] Slurry preparation: 5 mg catalyst (carbon material prepared in different embodiments), 550 µL ultrapure water, 400 µL isopropanol, 50 µL Nafion (5 wt.%) mixed solution was ultrasonically dispersed at 20 °C for 60 min;
[0129] Working electrode preparation: 10 µL of catalyst slurry was added dropwise to an area of 0.2475 cm 2 The surface of the glassy carbon electrode was dried naturally;
[0130] Preparation of oxygen-saturated electrolyte: Accurately weigh 4g of sodium hydroxide and stir to dissolve it in 1L of ultrapure water, then introduce high-purity oxygen for 30 minutes until the dissolved oxygen in the electrolyte reaches saturation.
[0131] Electrochemical testing:
[0132] 100mL of oxygen-saturated electrolyte was placed in a five-mouth reaction bottle, and high-purity oxygen was continuously pumped in during the test. A graphite rod was used as the counter electrode and a mercury / mercury oxide electrode was used as the reference electrode. First, 100 cycles of cyclic voltammetry were performed until the electrode surface reached a quasi-steady state. Then, a polarization curve test was performed (the ring electrode oxidation voltage was constant at 1.2V vs RHE, and the electrode speed was 1600rpm). The polarization curves needed to be measured repeatedly until they completely overlapped. The electrolyte needed to be replaced each time the sample was changed.
[0133] 2. Two-electrode flow-through electrolyzer test (evaluation of catalyst activity and stability under high current)
[0134] Gas diffusion electrode preparation:
[0135] Slurry preparation: 80 mg of catalyst (carbon material prepared in different embodiments), 4 mL of ultrapure water, 3.2 mL of ethanol, 0.8 mL of polytetrafluoroethylene aqueous solution (5 wt.%), constant temperature ultrasonic dispersion at 20°C for 60 min.
[0136] Electrode preparation: Ultrasonic spraying technology is used to evenly load the catalyst slurry on carbon paper 2*2cm 2 The center area (the size of the carbon paper used is 3*3cm 2 ); the catalyst loading is 4 mg / cm 2 .
[0137] Electrolyte preparation: Accurately weigh 500g of sodium hydroxide and stir to dissolve it in 5L of ultrapure water.
[0138] Electrochemical test: 2*2cm 2 The commercial nickel foam was used as the anode; the cathode was a homemade gas diffusion electrode; the side of the carbon paper sprayed with the catalyst was in contact with the electrolyte, and the back of the carbon paper was directly in contact with the air (the air was used as the oxygen source for the oxygen reduction reaction); the cathode / anode chambers were separated by a commercial proton membrane; the distance between the anode and cathode electrodes was 2 mm.
[0139] Pour the prepared 5L electrolyte into the anode tank, and add 5L ultrapure water into the cathode tank; turn on the constant temperature water tank and control the temperature of the electrolyte tank at 20°C. Turn on the peristaltic pump to fill the cathode / anode chambers with water and electrolyte respectively; the flow rate of the cathode / anode chambers is 20mL / min; after connecting the electrodes, turn on the electrochemical workstation and charge at 300mA / cm 2 The current density was used for constant current electrolysis test (anode reaction: 2NaOH→1 / 2O2+H2O+2Na + +2e - ; Cathode reaction: O2+2H2O+2Na + +2e -→H2O2+2NaOH); the concentration of hydrogen peroxide in the cathode chamber was tested every 10 hours; the concentration of hydrogen peroxide in the cathode electrolyte was determined by potassium titanium oxalate spectrophotometry.
[0140] Test Results
[0141] Table 2 Orthogonal experimental results of PECVD oxygen-doped carbon materials in Examples 1 to 9
[0142]
[0143] From the range analysis R value in Table 2, it can be seen that the atmosphere and reaction temperature in the PECVD reaction are the most important factors affecting the electrocatalytic activity and selectivity of oxygen-doped carbon materials, while the plasma RF power has little effect on the catalyst performance. From the average K value, it can be seen that the most preferred atmosphere should be CO2 / Ar, the most preferred reaction temperature should be 300°C, and the most preferred RF power should be 100W.
[0144] The “initial carbon” mentioned below is the carbon black (XC-72R, Cabot Corporation) used in the examples.
[0145] Figure 1 is the oxygen reduction polarization curve and hydrogen peroxide selectivity curve of different carbon materials; Figure 1 It can be seen that oxygen doping can significantly improve the oxygen reduction electrocatalytic activity and hydrogen peroxide selectivity of carbon materials. However, due to the different preparation process parameters, the electrocatalytic performance of the oxygen-doped carbon materials obtained in Examples 3 and 6 is much higher than that of the oxygen-doped carbon materials prepared in Example 9. Compared with oxygen doping, nitrogen doping has a relatively weaker effect on carbon materials (Examples 12 and 14), but oxygen-nitrogen co-doping (Example 16) shows the best oxygen reduction electrocatalytic activity and hydrogen peroxide selectivity. This shows that oxygen or nitrogen doping has a synergistic effect, which can further improve the electrocatalytic performance of oxygen-doped carbon materials.
[0146] Figure 2 TEM images of different carbon materials. Figure 2 It can be seen that after the carbon nanoparticles are treated with carbon dioxide plasma (Example 6), the number of graphite layers is significantly reduced, forming hollow carbon nanoparticles. This is because carbon dioxide gas produces a large amount of active oxygen free radicals and CO free radicals after radio frequency excitation, which produce violent ablation reactions with the carbon surface under high temperature environment, generating gases such as carbon dioxide or carbon monoxide, resulting in thinning of the graphite layer. The formation of this special structure is conducive to increasing the electrochemical active specific surface area ( Figure 3 ), which strengthens the mass transfer process of the oxygen reduction reaction and is beneficial to the improvement of the electrocatalytic performance of oxygen-doped carbon materials.
[0147] X-ray photoelectron spectroscopy (XPS) is used to reveal the intrinsic relationship between the catalytic performance of various oxygen-doped carbon materials and their oxygen-doped geometric configuration.
[0148] Figure 4 is the O1s fine spectrum of different carbon materials; Figure 4 From the O1s fine spectrum, it can be seen that the content of carbonyl C=O (binding energy BE=531.0eV) in the sample treated at 300°C increased significantly compared with the oxygen-doped sample at room temperature. Moreover, the content of carbonyl C=O generated by the carbon dioxide plasma source is relatively high compared with that of oxygen / water plasma treatment. This is because the C=C double bond in the carbon material is relatively active and easily attacked by oxygen plasma to generate a CO bond; then the hydrogen atom is transferred from the adjacent chain to combine with the CO bond to produce a C-OH bond; in addition, under the action of oxygen plasma, a variety of other oxygen configurations can be formed through intramolecular recombination, including carboxyl oxygen, ester oxygen, ether oxygen and carbonyl oxygen. Compared with oxygen excitation, carbon dioxide excitation can produce a large amount of oxygen plasma and CO plasma. Therefore, in addition to the above-mentioned interaction between oxygen plasma and carbon material, CO plasma may form a carbonyl with a CCC=O configuration with the broken C=C bond, resulting in a relatively high carbonyl oxygen in the carbon material treated with carbon dioxide plasma.
[0149] Figure 5 is a graph showing the relationship between the carbonyl content and the electrocatalytic activity in the initial carbon material and the oxygen-doped carbon material prepared in Examples 1 to 9; Figure 5 It can be seen that the activity of oxygen-doped carbon materials shows a significant positive correlation with the carbonyl C=O content (half-wave potential E 1 / 2 Linear relationship with carbonyl content: y=0.058x+0.61,R 2 =0.90). The above experimental results prove that in a relatively high temperature environment and a carbon dioxide atmosphere, it is more conducive to the introduction of carbonyl C=O, which helps to obtain highly active and selective oxygen-doped carbon materials.
[0150] In summary, the high performance of oxygen-doped carbon materials mainly stems from the special hollow nanoparticle structure and the high content of carbonyl oxygen with high catalytic activity.
[0151] Table 3 Electrocatalytic activity and selectivity of nitrogen-doped carbon materials in Examples 10 to 14
[0152]
[0153] As shown in Table 3, the PECVD power has a weak effect on the electrocatalytic activity of nitrogen-doped carbon materials; however, as the PECVD reaction temperature increases, its electrocatalytic activity is significantly enhanced. It is worth noting that while the activity increases, its hydrogen peroxide selectivity also decreases.
[0154] Figure 6 N1s fine spectra of different carbon materials; Figure 6The XPS results show that nitrogen atoms have been successfully introduced into the lattice of the carbon material. At room temperature, nitrogen atoms mainly exist in the form of pyridinic nitrogen and pyrrolic nitrogen, with an atomic ratio of about 0.5. However, as the reaction temperature increases to 300°C, the pyridinic nitrogen / pyrrolic nitrogen atomic ratio increases to 1.3, indicating that the pyridinic nitrogen content increases significantly. The above experimental results show that nitrogen doping can effectively improve the electrocatalytic activity of carbon materials, and increasing the pyridinic nitrogen content is more beneficial to its electrocatalytic activity. However, its hydrogen peroxide selectivity decreases due to the increase in pyridinic nitrogen content.
[0155] After determining the geometric relationship between each process parameter and the introduced oxygen / nitrogen, the present invention synthesizes an oxygen / nitrogen atom co-doped carbon material with a specific geometric configuration, introduces nitrogen atoms into the oxygen-doped carbon material lattice, and synthesizes oxygen-nitrogen co-doped hollow carbon nanoparticles (Examples 15-18). The results are shown in Table 4.
[0156] Table 4 Electrocatalytic activity and selectivity of oxygen-nitrogen co-doped hollow carbon nanoparticles in Examples 15-18
[0157]
[0158] From Table 4 and Figure 1 It can be seen that compared with single oxygen doping (Example 6) or nitrogen doping (Example 14), oxygen-nitrogen co-doped hollow carbon nanoparticles have higher electrocatalytic activity and show a fairly high hydrogen peroxide selectivity. It is worth noting that increasing the nitrogen doping reaction temperature is conducive to obtaining more active oxygen-nitrogen doped carbon materials. However, increasing the duration of the oxygen doping reaction, the electrocatalytic performance of the oxygen-nitrogen co-doped hollow carbon nanoparticles remains basically unchanged. This may be because after increasing the oxidation time, the introduced oxygen content has reached the upper limit, and no more active sites will be generated. Instead, it will aggravate the graphite layer thinning process (Example 18, Figure 2 ).
[0159] Figure 7 The O1s and N1s spectra of oxygen-nitrogen co-doped hollow carbon nanoparticles prepared in Example 16. Figure 7 It can be seen that the geometric configurations of its oxygen and nitrogen atoms are substantially consistent with those of Example 6 and Example 14, respectively, ensuring its excellent intrinsic electrocatalytic performance.
[0160] Figure 8 is a graph showing the cell pressure and hydrogen peroxide selectivity in the oxygen-nitrogen co-doped hollow carbon nanoparticles prepared in Example 16 as a function of time; Figure 8 It can be seen that high current density (300mA / cm 2 ), the cell pressure of the electrolyzer was basically stable, and the selectivity of hydrogen peroxide was maintained at about 95%. This shows that the oxygen-nitrogen co-doped hollow carbon nanoparticles of the present invention have excellent two-electron oxygen reduction electrocatalytic activity, hydrogen peroxide selectivity and stability.
[0161] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing oxygen-nitrogen co-doped hollow carbon nanoparticles, characterized in that: The following steps are involved: Using plasma enhanced chemical vapor deposition method: In an oxygen-containing atmosphere, carbon nanoparticles are first deposited, and oxygen-doped hollow carbon nanoparticles are obtained by ablation of oxygen-containing plasma; In a nitrogen-containing atmosphere, subjecting the oxygen-doped hollow carbon nanoparticles to a second deposition to obtain oxygen-nitrogen co-doped hollow carbon nanoparticles; The surface graphite layer thickness of the oxygen-nitrogen co-doped hollow carbon nanoparticles is 5 to 100 atomic layers, and the cavity width is 5 to 50 nm; In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of the doped oxygen atoms is 1-12%, and the molar content of the carbonyl oxygen atoms in the doped oxygen atoms in the oxygen-nitrogen co-doped hollow carbon nanoparticles is 0.5-3%; the XPS binding energy of the carbonyl oxygen is BE=531.0 eV; The content x of the carbonyl oxygen atom and the electrocatalytic activity y satisfy the following functional relationship: y=0.058x+0.61, R 2 =0.90; where y is the half-wave potential E 1 / 2 V vs. RHE meter; In the oxygen-nitrogen co-doped hollow carbon nanoparticles, the molar content of the doped nitrogen atoms is 1-4%, the molar percentage of pyridinic nitrogen and pyrrolic nitrogen in the doped nitrogen atoms accounts for 50-80% of the total nitrogen atoms, and the molar ratio of pyridinic nitrogen to pyrrolic nitrogen is 0.5-2:1; The oxygen-containing atmosphere includes one or more of oxygen-argon, carbon dioxide-argon, and water vapor-argon; The nitrogen-containing atmosphere includes nitrogen or ammonia; The conditions of the first deposition and the second deposition independently include: plasma RF power of 100-500W, vacuum degree of 10-100Pa, sample tube speed of 50-100rpm, temperature of 300-500°C, and time of 10-60min.
2. The preparation method according to claim 1, characterized in that: The carbon nanoparticles are conductive carbon black, and the particle size of the conductive carbon black is 10-200 nm.
3. The preparation method according to claim 1, characterized in that: The volume fraction of argon in the oxygen-containing atmosphere is 50-90%; the flow rate of the oxygen-containing atmosphere is 20-200 mL / min.
4. The preparation method according to claim 1, characterized in that: The flow rate of the nitrogen-containing atmosphere is 20-200 mL / min.
5. Oxygen-nitrogen co-doped hollow carbon nanoparticles prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the oxygen-nitrogen co-doped hollow carbon nanoparticles according to claim 5 in electrosynthesis of hydrogen peroxide.
Citation Information
Patent Citations
Application of oxygen-doped carbon material in electro-catalytic synthesis of hydrogen peroxide
CN115852424A
Preparation method and application of boron / nitrogen co-doped carbon catalyst for electrocatalytic synthesis of hydrogen peroxide
CN117144395A
High-selectivity H2O2 electrosynthesis carbon-based catalyst as well as preparation method and application thereof
CN117431559A
Plasma oxygen-doped activated carbon catalyst as well as preparation method and application thereof
CN117926285A
Oxygen and nitrogen co-doped polyacrylonitrile-based carbon fiber and preparation method thereof
CN104838051A